The densification of hydroxyapatite from eggshell waste at different sintering temperature / Natasha Ahmad Nawawi ... [et al.] - Ahmad Nawawi, Natasha; Ahmad, Nur Natrah Auni; Nurul Hidayah Imaniah Noor Hamdan, Nurul Hidayah Imaniah; Le Thi Bang, Le Thi Bang (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The outstanding biocompatibility and bioactivity properties of hydroxyapatite (HA) as a bio-implant material have garnered significant attention in prompting its extensive study. However, due to its brittleness and lower strength, its usage as a bone implant in load-bearing regions of biomedical applications is limited. The mechanical performance of the HA bodies is decreased by transformation-induced cracking as well as uncontrolled grain development. However, sintered HA ceramics with superior mechanical characteristics may be created if the prepared powder has better powder attributes including stoichiometry, crystallinity, agglomeration, and morphology from the start. Thus, this research explored the preparation of HA from discarded eggshells as a source of calcium via the dry reaction method and the correlation between its sinterability, densification, and mechanical properties at various sintering temperatures. In this work, the calcined eggshell powder was mixed with Calcium Hydrogen Phosphate Dihydrate (CHPD) via ball milling at 400 rpm speed for 4 hours and subsequently heat treated at 800 °C. The synthesized HA powder was compacted via hydraulic press and then sintered at temperatures of 1100 ℃, 1150 ℃, 1200 ℃, and 1250 ℃. The XRD analysis of the sintered HA samples revealed that the phase stability of the HA phase remained unaffected up to 1250 °C. Similar trends of average grain size, relative density, and hardness to sintering temperature were observed. HA samples sintered at 1250 °C exhibited the optimum mechanical properties with a relative density of 90.72% and a hardness of 4.34 GPa. It is believed that the grain boundary diffusion through the densification mechanism does not reach a densification level that is conducive to grain growth. Hence, the hardness still increased although the densification was relatively low. It can be concluded that HA densification significantly influences the grain coarsening and mechanical properties of the eggshell-derived HA.